Bone involvement in adult patients affected with Ehlers-Danlos syndrome. Issue 8 (August 2016) - Eller-Vainicher, C.; Bassotti, A.; Imeraj, A.; Cairoli, E.; Ulivieri, F.; Cortini, F.; Dubini, M.; Marinelli, B.; Spada, A.; Chiodini, I.
Abstract Summary The Ehlers-Danlos syndrome is characterized by abnormal connective tissue but bone involvement is debated. We found a reduced BMD and bone quality and increased prevalence of asymptomatic vertebral fractures in eugonadal patients with Ehlers-Danlos syndrome. These findings suggest the need of a bone health evaluation in these patients. Introduction The Ehlers-Danlos (EDS) syndrome is characterized by abnormalities of the connective tissue leading to ligamentous laxity and skin and tissue fragility. We evaluated the bone metabolism, bone mineral density (BMD) and bone quality (measured by trabecular bone score, TBS), and the prevalence of vertebral fractures (VFx) in a group of eugonadal adult EDS patients. Methods Fifty consecutive Caucasian patients, aged 30–50 years (36 females, 14 males) with classical or hypermobility EDS and 50 age-, gender-, and body mass index (BMI)-matched control subjects were enrolled. In all subjects' calcium-phosphorous metabolism, bone turnover, BMD at the lumbar spine (LS) and femur (femoral neck, FN and total femur, FT) and TBS by dual-energy X-ray absorptiometry, and the VFx presence by spine radiograph were assessed. Results Patients showed reduced BMD (Z-scores LS −0.45 ± 1.00, FN −0.56 ± 1.01, FT −0.58 ± 0.92) and TBS (1.299 ± 0.111) and increased prevalence of morphometric VFx (32 %) than controls (Z-scores LS 0.09 ± 1.22, FN 0.01 ± 0.97, FT 0.08 ± 0.89; TBS 1.382 ± 0.176; VFx 8 %, p <0.05 for all comparisons), while vitamin D levels, calcium-phosphorous metabolism, and bone turnover were comparable. Fractured EDS patients showed lower TBS values than non-fractured ones (1.245 ± 0.138 vs 1.325 ± 0.086, p  < 0.05), despite comparable BMD. In EDS patients, the VFx presence was significantly associated with TBS even after adjusting for sex, age, BMD, EDS type, and falls frequency. Conclusions EDS patients have reduced BMD and bone quality (as measured by TBS) and increased prevalence of VFx.